Comparative federalism : constitutional arrangements and case law - Palermo, Francesco; Kössler, Karl, 1979- (Hart studies in comparative public law, 2017)
This is the first comprehensive book that explores the subject of federalism from the perspective of comparative constitutional law, whilst simultaneously placing a strong emphasis on how federal systems work in practice. This focus is reflected in the book's two most innovative elements. First, it analyses from a comparative point of view how government levels exercise their powers and interact in several highly topical policy areas like social welfare, environmental protection or migrant integration. Second, the book incorporates case law boxes discussing seminal judgments from federal systems worldwide and thus demonstrates the practical impact of constitutional jurisprudence on policymakers and citizens alike. "This is simply the best analysis of contemporary federalism currently available. It is comprehensive in its coverage, thorough in its analysis, and persuasive in its conclusions. Every student of federalism, from novice to expert, will find benefit from this volume." Professor G Alan Tarr, Rutgers University "Wading through the thicket of the multiple forms that the federal idea has taken in the contemporary world, this remarkably comprehensive treatise backed by case law fills a long-awaited gap in the literature on comparative federalism. It combines a mastery of the literature on federal theory with a critical understanding of how it plays out in practice. Outstanding in the breadth of its scope, this magisterial survey will serve as a work of reference for generations of scholars who seek to understand how federalism works in developed as well as developing countries." Professor Balveer Arora, Jawaharlal Nehru University New Delhi "This book is an extraordinarily handy work of reference on the diverse federal-type systems of the world. It handles both shared principles and differences of perspective, structure or practice with confidence and ease. It will become a standard work for scholars and practitioners working in the field." Professor Cheryl Saunders, The University of Melbourne "This is a remarkable book - for its sheer breadth of scope, combining detail of practice with analysis of federal principles, and for its fresh look at federalism. With great erudition, drawing on world scholarship and the practice of federalism across the globe, Palermo and Kössler magnificently traverse from the ancient roots of federalism to the contemporary debates on ethno-cultural dimensions and participatory democracy. The book sets a new benchmark for the study of comparative federalism, providing new insights that are bound to influence practice in an era where federal arrangements are expected to deliver answers to key governance and societal challenges." Professor Nico Steytler, University of the Western Cape.